Guía gastronómica del cantón Pujilí de la provincia de Cotopaxi. - Pambi Pambi, Verónica Jacqueline (2021)
In the present research project began with the realization of the situational diagnosis in the Pujili canton, Cotopaxi province. In order to know the current situation in which we find the four scopes: sociocultural, economic, environmental and touristic the same that contributed with positive results for the development of the investigation. The information collected in the different parishes GADs and the Development and Territorial Planning Plan of the year 2014 (PDOT). It is essential to mention that in the Pujili canton the main economic activity is agriculture, livestock, forestry which comprises 71% in the rural area, while 29% in the urban area dedicated different activities such as: building, commerce, education, manufacturing among others. The Pujili canton is composed of 7 parishes, 1 urban and 6 rural, in which the Pujili parish has the majority of the population with 48, 41% of total population. The methodology that was used is qualitative, which implied techniques such as direct observation, interview and question guide that helped in the development of the investigation. In addition an inventory for all this, the files extracted from INPC (National Institute of Culture Heritage), A4 Knowledge and uses related to nature and the universe, resulting in 13 gastronomic processes of which 6 dishes affected to festivity gastronomic and 7 dishes affected to daily gastronomic. The files contain all the guidelines to the data that was needed for the inventory with this salvation of the same can be establish. Finally, the result of research is the design of Gastronomic Guide of Pujili canton; this was possible thanks to the collaboration of the key actors that provided detailed information of ingredients and how to prepare each dishes. With this research is expected to contribute to the next investigations that arise in the canton, to rescue the valorization and dissemination of immaterial culture heritage facing the new market trends.